Frequent loss of SMAD4/DPC4 protein in colorectal cancers. Issue 6 (1st December 2002) - Salovaara, R; Roth, S; Loukola, A; Launonen, V; Sistonen, P; Avizienyte, E; Kristo, P; Järvinen, H; Souchelnytskyi, S; Sarlomo-Rikala, M; Aaltonen, L A
Abstract : Background and aims: Loss of DNA sequences from chromosome 18q21 is a major genetic change in colorectal tumorigenesis. Multiple genes have been identified in this area. One of these, DPC4 ( deleted in pancreatic cancer 4, also known as SMAD4 ), is mutated in a minor subset of colorectal carcinomas as well as in germlines of humans predisposed to colon tumours. Patients and methods: The involvement of SMAD4 in sporadic colorectal neoplasia was evaluated by immunohistochemistry in 53 unselected cases and 27 cases displaying microsatellite instability. Results: SMAD4 expression was absent in 20 of 53 (38%) unselected colorectal carcinomas, and reduced in another 15 (28%) cases. However, 26 of 27 cancers displaying microsatellite instability and TGF-βIIR mutations were positive for SMAD4 immunostaining. Conclusions: Loss of SMAD4 expression may play a more prominent role in colon cancer than anticipated based on genetic evidence, but not in mutator phenotype tumours.